Technical and economic analysis of electricity generation from forest, fossil, and wood-waste fuels in a Finnish heating plant - Palander, Teijo (Energy (Oxford), 2011)
The Finnish energy industry is subject to policy decisions regarding renewable energy production and energy efficiency. Conventional electricity generation has environmental side-effects that may cause global warming. Renewable fuels are superior because they offer near-zero net emissions. In this study, I investigated a heating mill’s ability to generate electricity from forest fuels in southern Finland on a 1-year strategic decision-making horizon. I solved the electricity generation problem using optimization of the energy products and fuel mixtures based on energy efficiency and forest technology. The decision environment was complicated by the sequence-dependent procurement chains for forest fuels. The optimal product and fuel mixtures were selected by minimizing procurement costs, maximizing production revenues, and minimizing energy losses. The combinatorial complexity of the problem required the use of adaptive techniques to solve a multiple-objective linear programming system with industrial relevance. I discuss the properties of the decision-support system and methodology and illustrate pricing of electricity generation based on real industrial data. The electricity-generation, -purchase, and -sales decisions are made based on a comprehensive technical and economic analysis that accounts for procurement of local forest fuels in a holistic supply chain model. ► I use adaptive techniques to solve a multiple-objective linear programming system with industrial relevance. ► I investigated a heating mill’s ability to generate electricity from forest fuels. ► The electricity-generation, -purchase, and -sales decisions are made based on a comprehensive technical and economic analysis. ► The optimal product and fuel mixtures were selected by minimizing procurement costs, maximizing production revenues, and minimizing energy losses.